Mechanical response of carbon/epoxy composite sandwich structures with three-dimensional corrugated cores. (1st March 2018) - Xu, Guo-dong; Wang, Zhi-hai; Zeng, Tao; Cheng, Su; Fang, Dai-ning
Abstract: A novel three-dimensional (3D) corrugated core sandwich structure was designed and fabricated by auto-cutting process. Mechanical behaviors and failure mechanism of 3D corrugated core sandwich structures were investigated. Analytical models were developed to estimate the strength, stiffness and dominant failure modes. In order to demonstrate sensitivity of the graded parameters on mechanical behaviors of 3D corrugated core sandwich structures, the specimens with different graded parameters were fabricated and tested under compression and bending loads. Results showed that the graded parameters have obviously influences on the mechanical properties and failure modes of 3D corrugated core sandwich structures. The predictions were also compared with the experiments and the results showed good agreements. Failure maps were constructed to illustrate the controlling failure mechanisms in various regions with different parameters.